2010
DOI: 10.1159/000268108
|View full text |Cite
|
Sign up to set email alerts
|

Giant Haemangioma of the Liver: Observation or Resection?

Abstract: Background: Haemangiomata are the most frequent benign solid liver lesion. The management of giant (≧5 cm) haemangiomata of the liver remains controversial. Methods: A search of relevant peer-reviewed literature was conducted using PubMed and original articles were reviewed. Results and Conclusions: The vast majority of giant haemangiomata remain asymptomatic and have a benign and uncomplicated natural history. Decisions regarding the optimal management of giant haemangiomata depend on a high level of confiden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
88
0
14

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(104 citation statements)
references
References 52 publications
2
88
0
14
Order By: Relevance
“…Considering the benign and non-progressive nature of the dis- ease, it is currently accepted that a giant hemangioma is not necessarily an indication for surgery just because of its size, and continued observation in asymptomatic patients or patients with minimal abdominal symptoms seems to be justified [19,20] . Surgery remains the only consistently effective curative treatment for giant hemangiomas and should be considered for patients with established complications, diagnostic uncertainty and incapacitating symptoms, where operative risk is acceptable, or where the diagnosis remains uncertain despite appropriate specialist investigation [21] . Various other treatment methods have been reported but their long-term results have been poor [20] .…”
Section: Discussionmentioning
confidence: 99%
“…Considering the benign and non-progressive nature of the dis- ease, it is currently accepted that a giant hemangioma is not necessarily an indication for surgery just because of its size, and continued observation in asymptomatic patients or patients with minimal abdominal symptoms seems to be justified [19,20] . Surgery remains the only consistently effective curative treatment for giant hemangiomas and should be considered for patients with established complications, diagnostic uncertainty and incapacitating symptoms, where operative risk is acceptable, or where the diagnosis remains uncertain despite appropriate specialist investigation [21] . Various other treatment methods have been reported but their long-term results have been poor [20] .…”
Section: Discussionmentioning
confidence: 99%
“…They are most often seen in the liver. [9][10][11] The incidence of hemangiomas varies from 0.4% to 20%. [1][2][3]6 Hemangioma are often seen between the ages of 30 and 50 years and 5 to 6 times more often in women than in men.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3]6 Hemangioma are often seen between the ages of 30 and 50 years and 5 to 6 times more often in women than in men. 4,6,7,9,10 Therefore, it has been suggested that there may be a relationship between the disease and the use of exogenous steroids or female-specific hormones, although the relationship has not been clearly shown. 2,3,10 Because most hepatic hemangioma are asymptomatic, they are often recognized incidentally during radiologic tests for other reasons.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations